Maintaining Service Quality: The Important Role of Operator Performance in Educational Institutions - Ginanjar Wira Saputra; Kurniawati Kurniawati; Riza Bahtiar Sulistyan; Bhawna Bhawna (Mahameru Publisher, 2023)
The purpose of this research is to identify and analyze the important role of the performance of educational institution operators in maintaining service quality. The method used is descriptive analytical research through a quantitative approach. The samples taken were 40 elementary school operator employees in Bandung city. The results of the study conclude that the performance of the elementary school operator employees in Bandung city is good and their work results can be relied upon. Performance plays an important role in improving the quality of service for employees of the elementary school operators in Bandung city. An important implication in this study is that employees have punctuality in completing work, the quality of work can be relied upon and accounted for, have a high ability to complete work, be able to communicate well between leaders and teachers, and have high initiative in completing work and solving problems.